Islam And Anti-Corruption: Development Of Anti-Corruption Education Materials From A Religious Perspective - Yuwanamu, Irham; Haq, Sansan Ziaul (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
Corruption is one of the most important variables in a country's decline. The Indonesian state established the Corruption Eradication Commission (KPK-Komisi Pemberantasan Korupsi) to address this. One of its roles is prevention, so the KPK has an anti-corruption education program. Unfortunately, this program has not integrated religious values, even though Indonesia is a religious and predominantly Muslim society. This article examines anti-corruption education from an Islamic perspective. This study seeks to integrate anti-corruption education with an Islamic perspective. This study uses a thematic-analytical method whose primary source is the Quran, interpreted from various commentaries. The findings show that, in substance, the Qur'an has taught us not to commit corruption. Phrases found in the Qur'an whose meaning is commensurate with corruption are 'eating other people's property unlawfully' (akl amwal al-nas bi-al-batil), 'eating illegally' (akl al-suht), and bribing judges (al-idla' ila-al-hukkam). This study further shows that corruption falls into the category of unlawful taking away other people's rights, while bribery is one of the doors to this unjust act. Therefore, corruption is a grave sin that will have serious consequences hereafter. The findings of this study can further contribute to the development of anti-corruption education from an Islamic perspective.